Polyester-based resistant adhesive
By adding trace amounts of silicone resin to the polypropylene resin to improve its heat resistance and adjusting the laminated structure, the problems of hollow crumbs and film performance degradation are solved, and excellent effects of lightweight, film forming and whiteness are achieved.
Patent Information
- Application Number
- CN202380060923.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-22
- Filing Date
- 2023-07-05
- Publication Date
- 2025-04-29
AI Technical Summary
When using polypropylene resin as a cavitation manifester, the prior art tends to cause hollow rupture, poor lightweight and buffering properties, and poor heat resistance of surfactants and polyethylene glycol, resulting in a decrease in the whiteness of the film and deterioration of film forming properties.
By adding an extremely small amount of silicone resin to the polypropylene resin, the heat resistance of the polypropylene dispersed particles in the polyester resin is improved, deformation during heating and stretching is reduced, and side effects are suppressed by adjusting the laminated structure and the amount of silicone resin added.
In the case where the polypropylene resin is kept as a hollow expressing agent, a hollow-containing polyester-based easy-adhesive film with excellent light weight, film-forming properties, concealment and whiteness is achieved, and deterioration of coating properties and printing properties is suppressed.
Smart Images

Figure BDA0005278730380000281
Abstract
Description
Technical Field
[0001] The present invention relates to a void-containing polyester-based easy-adhesion film containing voids inside. Background Art
[0002] As a method for obtaining a film having a function similar to that of paper, a method of making a film contain a large number of fine cavities inside is known.
[0003] In this method, an incompatible thermoplastic resin (hereinafter referred to as an incompatible resin) is mixed with a polyester resin to obtain a sheet in which the incompatible resin is dispersed in the polyester resin, and the sheet is stretched at least along a uniaxial direction. Thus, this method causes voids to be visualized by interfacial peeling between the polyester resin and the incompatible resin. As such incompatible resins, for example, polyolefin resins such as polyethylene resins, polypropylene resins, and polymethylpentene resins (for example, see patent documents 1 to 3), and polystyrene resins (for example, see patent documents 4 and 5) have been proposed. Among them, polypropylene resins are excellent in terms of void visualization and cost performance.
[0004] Here, when the polypropylene resin is simply dispersed in the polyester resin, the dispersion diameter of the polypropylene dispersed particles becomes larger. Therefore, the voids are easily visible, but on the other hand, the voids become larger, and sufficient concealment cannot be obtained, and the film forming property also deteriorates. Therefore, a method of microdispersing the polypropylene resin has begun to be adopted. So far, as a method for the microdispersion, a method of adding a dispersant such as a surfactant and polyethylene glycol has been proposed (for example, refer to Patent Documents 6 and 7).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 49-134755
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2-284929
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 2-180933
[0010] Patent Document 4: Japanese Patent Publication No. 54-29550
[0011] Patent Document 5: Japanese Patent Application Laid-Open No. 11-116716
[0012] Patent Document 6: Japanese Patent Publication No. 7-17779
[0013] Patent Document 7: Japanese Patent Application Laid-Open No. 8-252857 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] However, when a dispersant such as a surfactant or polyethylene glycol is added, although it has a micro-dispersion effect on the polypropylene resin, the polypropylene resin will deform during the heating and stretching process and the heat fixing process. Therefore, the resulting voids are also easily collapsed, and sufficient lightness and cushioning properties cannot be obtained. In addition, surfactants and polyethylene glycol have poor heat resistance, so they are prone to thermal degradation during the melt extrusion process with polyester resin, and the whiteness of the resulting film will decrease. Depending on the situation, there is a problem of promoting the degradation of the polyester resin and worsening the film-forming properties.
[0016] Furthermore, in recent years, in the printing industry, printing speed has been gradually increased, and higher adhesion with respect to UV curing inks and the like has been sought.
[0017] The present invention aims to improve the above-mentioned problems of the prior art and provide a void-containing polyester-based easy-adhesion film having excellent lightness, film-forming properties, hiding power, whiteness and easy adhesion even when polypropylene resin is mainly used as a void-developing agent.
[0018] Solutions for solving problems
[0019] As a result of in-depth research conducted by the inventors, the following conclusions were found by adding a very small amount of silicone resin to polypropylene resin. That is, the inventors found that the heat resistance of the dispersed polypropylene particles in the polyester resin can be improved, and the deformation of the dispersed polypropylene particles during heating, stretching and heat fixing can be reduced. As a result, the inventors found that a polyester-based easy-to-bond film containing voids with excellent lightness, film-forming properties, concealment and whiteness can be obtained. Furthermore, the inventors found that by adjusting the stacking structure and the amount of silicone resin added, the side effects of the silicone resin, namely, the deterioration of the coating and printability, can be suppressed.
[0020] That is, the void-containing polyester-based easy-adhesion film of the present invention has the following configuration.
[0021] 1. A void-containing polyester-based easy-adhesive film, comprising a first covering layer B1, a void-containing layer A, and a second covering layer B2 laminated in sequence, wherein the first covering layer B1 comprises a polyester resin containing an inorganic pigment, the void-containing layer A contains voids inside, the second covering layer B2 comprises a polyester resin containing an inorganic pigment, and a functional easy-adhesive layer is provided on the first covering layer B1.
[0022] The apparent density of the void-containing polyester easy-adhesive film is 0.80 g / cm 3 Above and 1.20g / cm 3 the following,
[0023] The void-containing layer A includes a composition containing a polyester resin, a polypropylene resin, and a silicone resin.
[0024] 2. The void-containing polyester-based adhesive film according to item 1 above, wherein the content of polydimethylsiloxane in the silicone resin in the void-containing layer A is 1 ppm or more and 2500 ppm or less relative to the total mass of the void-containing layer A.
[0025] 3. The void-containing polyester-based adhesive film according to item 1 above, wherein in the void-containing layer A, the content of polydimethylsiloxane in the silicone resin is 0.005% by mass or more and 2.000% by mass or less relative to 100% by mass of the polypropylene resin.
[0026] 4. The void-containing polyester-based easy-adhesion film according to item 1 above, wherein the inorganic pigment in the first covering layer B1 and the second covering layer B2 is titanium oxide.
[0027] 5. The void-containing polyester-based easy-to-bond film according to item 1 above, wherein the ratio of the sum of the thickness of the first covering layer B1 and the thickness of the second covering layer B2 to the sum of the thickness of the first covering layer B1, the thickness of the void-containing layer A and the thickness of the second covering layer B2 is greater than 6% and less than 40%.
[0028] 6. The void-containing polyester-based easy-adhesion film according to the above Item 1, wherein the total light transmittance is 1% to 30%.
[0029] 7. The void-containing polyester-based adhesive film according to item 1 above, wherein the apparent density is 0.80 g / cm 3 Above and 1.10g / cm 3 the following.
[0030] 8. The void-containing polyester-based adhesive film according to item 1 above, wherein the functional adhesive layer has a residual adhesion area of 99% or more as measured by the following evaluation method.
[0031] The remaining area of the seal is evaluated based on the following method:
[0032] The functional easy-adhesive layer of the polyester-based easy-adhesive film containing voids was printed using UV ink [T&K TOKA Co., Ltd., trade name "BEST CURE (registered trademark) UV161 Blue S"] using a printer [Ming Manufacturing Co., Ltd., trade name "RI TESTER"], and then the film coated with the ink layer was irradiated with 40 mJ / cm using a high-pressure mercury lamp. 2The ultraviolet light was used to cure the ultraviolet curing ink. Next, a 24 mm wide and 50 mm long piece of cellophane adhesive tape (CT405AP-24) manufactured by NICHIBAN was cut and completely attached using a hand-held rubber roller in a manner that prevented air from entering the surface of the ink layer. Afterwards, the cellophane adhesive tape was peeled off vertically, and the residual area (closely adhered residual area) of the printed layer was observed and calculated in an area of 24 mm × 50 mm (%).
[0033] 9. The void-containing polyester-based adhesive film according to item 1 above, wherein the functional adhesive layer contains an antistatic agent and has a surface resistivity of 1.0×10 13 Ω / sq or less.
[0034] 10. The void-containing polyester-based adhesive film according to item 1 above, wherein the number of pinhole-shaped shrinkage cavities in the functional adhesive layer is 5 pcs / m 2 the following.
[0035] (The number of pinhole-like shrinkage cavities in the functional adhesive layer was evaluated by visually observing the functional adhesive layer of the void-containing polyester adhesive film under a three-wavelength fluorescent lamp and counting the number of pinhole-like shrinkage cavities.)
[0036] 11. The void-containing polyester-based easy-adhesive film according to any one of items 1 to 10, which is used for labels, cards, packaging materials or release films.
[0037] Effects of the Invention
[0038] The present invention provides a void-containing polyester-based easy-adhesion film which is excellent in lightness, film-forming property, hiding property, whiteness, and adhesion to various inks and the like even when the film mainly contains a polypropylene resin as a void-developing agent. DETAILED DESCRIPTION
[0039] Hereinafter, the present invention will be described in detail.
[0040] The void-containing polyester-based easy-adhesive film of the present invention is preferably a laminated body in which a first covering layer B1, a void-containing layer A, and a second covering layer B2 are sequentially stacked, wherein the first covering layer B1 comprises a polyester resin containing an inorganic pigment, the void-containing layer A contains voids inside, and the second covering layer B2 comprises a polyester resin containing an inorganic pigment. The void-containing layer A is preferably formed of a composition containing a polyester resin, a polypropylene resin, and a silicone resin. In addition, the apparent density of the void-containing polyester-based easy-adhesive film is preferably 0.80 g / cm 3 Above and 1.20g / cm 3 the following.
[0041] The polyester resin that is the main component of the void-containing layer A, the first covering layer B1, and the second covering layer B2 is preferably a polymer synthesized from a dicarboxylic acid or an ester-forming derivative thereof and a diol or an ester-forming derivative thereof. Representative examples of such polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate. Among them, polyethylene terephthalate is preferred from the viewpoints of mechanical properties, heat resistance, cost, and the like.
[0042] In addition, other components may be copolymerized in these polyester resins as long as they do not impair the purpose of the present invention. Specifically, as copolymerization components, among the dicarboxylic acid components, isophthalic acid, naphthalene dicarboxylic acid, 4,4-diphenyl dicarboxylic acid, adipic acid, sebacic acid and ester-forming derivatives thereof may be listed. In addition, as diol components, diethylene glycol, hexamethylene glycol, neopentyl glycol and cyclohexanedimethanol may be listed. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol may also be listed. As for the copolymerization amount, it is preferably within 10 mol% relative to the constituent repeating units, and more preferably within 5 mol%.
[0043] As a method for producing a polyester resin, for example, it is preferred that the aforementioned dicarboxylic acid or its ester-forming derivative and diol or its ester-forming derivative are used as main starting materials, and then it is preferred that the polyester resin is produced by carrying out an esterification or transesterification reaction according to a conventional method and then further carrying out a polycondensation reaction under high temperature and reduced pressure.
[0044] From the viewpoint of film forming properties, recycling properties, etc., the intrinsic viscosity of the polyester resin is preferably 0.50 dl / g to 0.9 dl / g, and more preferably 0.55 dl / g to 0.85 dl / g.
[0045] The content of the polyester resin is preferably 70% by mass or more and 97% by mass or less, and more preferably 75% by mass or more and 95% by mass or less, relative to 100% by mass of the total of all components contained in the void-containing layer A. When the content of the polyester resin is 70% by mass or more, the void-containing polyester-based easy-adhesive film can suppress the deterioration of film-forming properties. When the content of the polyester resin is 97% or less, the void-containing polyester-based easy-adhesive film can form voids by adding polypropylene resin and silicone resin.
[0046] Next, the incompatible resin used as the void-revealing agent in the present invention, that is, the polypropylene resin, is described. The void-containing polyester-based easy-adhesive film of the present invention can maintain void-revealing properties by adopting a specific layer structure and using a specific polypropylene resin. As a result, the void-containing polyester-based easy-adhesive film of the present invention can obtain sufficient lightness and cushioning properties, and has excellent film-forming properties, concealing properties, and whiteness.
[0047] The polypropylene resin used in the present invention is preferably a crystalline polypropylene having 95 mol% or more, more preferably 98 mol% or more of propylene units, and particularly preferably a crystalline polypropylene homopolymer having 100 mol% of propylene units.
[0048] From the viewpoint of void visibility and film forming properties, the melt flow rate (MFR) of the polypropylene resin used in the present invention is preferably 1.0 g / 10 minutes or more and 10.0 g / 10 minutes or less, and more preferably 1.5 g / 10 minutes or more and 7.0 g / minute or less. When the MFR is 1.0 g / 10 minutes or more and 10.0 g / 10 minutes or less, the polypropylene dispersed particles become difficult to deform when extruded from the die, so it becomes easy to form voids. Furthermore, when the MFR is 1.0 g / 10 minutes or more and 10.0 g / 10 minutes or less, the dispersibility of the polypropylene dispersed particles is also excellent, sufficient concealment can be obtained, and the film forming properties are also excellent. In addition, the melt flow rate (MFR) is a measured value according to JIS K 7210 and under the conditions of 230°C and a load of 2.16 kg.
[0049] From the viewpoint of void visualization, the load deflection temperature of the polypropylene resin used in the present invention is preferably 85°C or more, more preferably 90°C or more, and further preferably 95°C or more. The upper limit does not need to be particularly limited, but is preferably 135°C or less. When the load deflection temperature is 85°C or more, especially in the longitudinal stretching process of heating and stretching the film at a temperature above the glass transition temperature of the polyester resin described later, the dispersed polypropylene particles are difficult to collapse, and thus, voids are easily formed. It should be noted that the load deflection temperature is a measured value according to the B method of JIS K 7191-1, 2 and when the bending stress of the test piece is 0.45 MPa.
[0050] From the viewpoint of void visualization, suppression of thermal degradation in the extrusion process and the recovery process, the weight average molecular weight (Mw) of the polypropylene resin used in the present invention is preferably 200,000 or more and 450,000 or less, more preferably 250,000 or more and 400,000 or less. When Mw is 450,000 or less, the dispersibility of the polypropylene dispersed particles becomes good, sufficient concealment can be obtained, and excellent film forming properties are obtained. When Mw is 200,000 or more, the polypropylene dispersed particles become difficult to deform, so it becomes easy to form voids. When Mw is 200,000 or more, even when recycled raw materials are used, it is possible to suppress the decrease in void visualization, so it is preferred.
[0051] In addition, the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn), i.e. molecular weight distribution (Mw / Mn) is preferably 2 or more and 6 or less, more preferably 2 or more and 5 or less. Mw / Mn is an index representing the width of molecular weight distribution, and the larger the value, the wider the molecular weight distribution. When Mw / Mn is 6 or less, low molecular weight components are reduced, so even when using recycled raw materials, the reduction of whiteness and void visibility can be suppressed, so it is preferred. In addition, if Mw / Mn is 2 or more, it is suitable for industrial production from the viewpoint of cost. It should be noted that weight average molecular weight (Mw) and number average molecular weight (Mn) are values measured using gel permeation chromatography (GPC).
[0052] From the viewpoint of void visualization and film forming properties, the content of the polypropylene resin is preferably 3% by mass or more and 30% by mass or less, and more preferably 5% by mass or more and 25% by mass or less, relative to 100% by mass of the total of all components contained in the void-containing layer A. When the content of the polypropylene resin is 3% by mass or more and 30% by mass or less, voids for obtaining sufficient lightness and cushioning properties can be formed, and film forming properties are excellent.
[0053] Examples of the silicone resin used in the present invention include silicone polymers, such as partially cross-linked silicone polymers (i.e., silicone resins in a narrow sense) and linear silicone polymers (i.e., silicone rubbers). Specifically, examples include methyl silicone resins, methylphenyl silicone resins, phenyl silicone resins, alkyd-modified silicone resins, polyester-modified silicone resins, urethane-modified silicone resins, epoxy-modified silicone resins, and acrylic-modified silicone resins. From the viewpoint of being able to withstand the extrusion temperature of the polyester resin as the base resin and the viewpoint of suppressing process contamination caused by sublimation, silicone resins having a cross-linked structure are preferred.
[0054] The method of adding the silicone resin is not particularly limited, and the silicone resin may be added directly by dry-mixing a powdery or pelletized material with the base resin. Alternatively, a masterbatch of a polyester resin, a polypropylene resin, and a silicone resin melt-mixed may be prepared in advance.
[0055] From the viewpoint of void visibility, film forming property, and manufacturing cost, the amount of silicone resin added is preferably 1 ppm or more and 10000 ppm or less relative to the total mass of the void-containing layer A, and more preferably 100 ppm or more and 8000 ppm or less. By setting it to more than 1 ppm, the apparent density can be efficiently reduced. By setting it to less than 10000 ppm, the deterioration of process pollution and film forming property can be suppressed. Furthermore, the manufacturing cost can be suppressed.
[0056] The content of polydimethylsiloxane derived from silicone resin is obtained according to the NMR (nuclear magnetic resonance) method. From the viewpoint of void visibility, film forming properties, and manufacturing cost, the content of polydimethylsiloxane derived from silicone resin is preferably 1 ppm or more and 2500 ppm or less relative to the total mass of the void-containing layer A, and more preferably 100 ppm or more and 2400 ppm or less. It is further preferably 100 ppm or more and 1400 ppm or less. By setting it to 1 ppm or more, the apparent density can be efficiently reduced. By setting it to 2500 ppm or less, it is possible to suppress process contamination and deterioration of film forming properties. Furthermore, it is possible to suppress manufacturing costs. Silicone resin has a cross-linked structure and is insoluble in solvents. Therefore, by using the NMR measurement method described later to obtain the content of polydimethylsiloxane present in the silicone resin, it can be used as an indicator of the content of the silicone resin in the void-containing layer A.
[0057] The content of polydimethylsiloxane in the silicone resin contained in the void-containing layer A obtained by the NMR method is preferably 0.005% by mass or more and 2.000% by mass or less relative to 100% by mass of the polypropylene resin in the void-containing layer A. More preferably, it is 0.010% by mass or more and 1.800% by mass or less. Still more preferably, it is 0.100% by mass or more and 0.800% by mass or less. By containing 0.005% by mass or more relative to 100% by mass of the polypropylene resin, the heat resistance of the polypropylene resin is improved, and it will not collapse during stretching, and can efficiently express voids. By setting it to 2.000% by mass or less, the deterioration of film forming properties can be suppressed.
[0058] By making the void-containing layer A contain a small amount of silicone resin, heat resistance can be imparted to the polypropylene resin. Therefore, it is possible to suppress thermal degradation of the polypropylene resin during material recycling and maintain void visualization. Even if a void-containing polyester-based easy-adhesive film is made, the voids are difficult to collapse in a high temperature environment, so that uneven thickness caused by local collapse of the polypropylene resin as a void visualization agent can be suppressed.
[0059] In addition, incompatible resins other than polypropylene resin may be contained within the range that does not impair the purpose of the present invention. The polypropylene resin preferably contains 90% by mass or more, more preferably 95% by mass or more, and most preferably 100% by mass relative to 100% by mass of the total incompatible resins in the void-containing layer A. In addition, from the viewpoint of whiteness and void visualization, it is preferred that dispersants such as polyethylene glycol and surfactants are not contained.
[0060] In addition, within the scope of not impairing the purpose of the present invention, these polyester resins or polypropylene resins may contain a small amount of other polymers, antioxidants, heat stabilizers, matting agents, pigments, ultraviolet absorbers, fluorescent whitening agents, plasticizers or other additives. In particular, in order to suppress the oxidative degradation of the polypropylene resin, it is preferred to contain an antioxidant or a thermal stabilizer. The types of antioxidants and thermal stabilizers are not particularly limited, and examples thereof include hindered phenol systems, phosphorus systems, hindered amine systems, etc., which can be used alone or in combination. As an added amount, it is preferably more than 1ppm and less than 50000ppm relative to the total mass of the void-containing layer A. It should be noted that in the present invention, even if a fluorescent whitening agent is not added to the void-containing layer A, excellent whiteness can be ensured.
[0061] In the present invention, for the polyester-based easy-to-bond film containing voids, in order to improve concealment and whiteness, inorganic pigments can be contained in polyester resin or polypropylene resin as required. As inorganic pigments, silicon dioxide, kaolinite, talc, calcium carbonate, zeolite, aluminum oxide, barium sulfate, titanium oxide, zinc sulfide, etc. can be listed. Among these, from the viewpoint of concealment and whiteness, titanium oxide, calcium carbonate, barium sulfate are preferably used. In addition, these inorganic pigments can be used alone, or two or more can be used in combination. These inorganic pigments can be included in the polyester-based easy-to-bond film containing voids by being added in advance in polyester resin or polypropylene resin.
[0062] The method of mixing the inorganic pigment into the polyester resin or the polypropylene resin is not particularly limited, and the following methods may be mentioned, namely, a method of dry-mixing the polyester resin and the polypropylene resin and directly feeding the mixture into a film-making machine; a method of dry-mixing the polyester resin and the polypropylene resin and then melt-mixing the mixture using various common mixers to form a masterbatch, etc.
[0063] The void-containing polyester-based easy-adhesive film of the present invention has a laminated structure in which a first covering layer B1, a void-containing layer A, and a second covering layer B2 are sequentially laminated, wherein the first covering layer B1 contains a polyester resin containing an inorganic pigment, the void-containing layer A contains voids inside, and the second covering layer B2 contains a polyester resin containing an inorganic pigment. Here, when the void-containing layer A containing a polypropylene resin is exposed on the surface layer, a part of the exposed polypropylene dispersed particles may be contaminated by the process such as roller contamination. In addition, by covering the void-containing layer A with the first covering layer B1 containing an inorganic pigment and the second covering layer B2, it is possible to prevent the whiteness from decreasing.
[0064] From the viewpoint of void visibility and suppression of exposure of polypropylene resin and silicone resin, the ratio of the total thickness of the first coating layer B1 and the thickness of the second coating layer B2 to the total thickness of the first coating layer B1, the thickness of the void-containing layer A, and the thickness of the second coating layer B2 (hereinafter sometimes referred to as the layer ratio) is preferably 6% or more and 40% or less, and more preferably 8% or more and 30% or less. When the layer ratio is 6% or more and 40% or less, the exposure of polypropylene resin and silicone resin can be suppressed, and the contact angle of water and the contact angle of diiodomethane can be reduced. Furthermore, when the layer ratio is 6% or more and 40% or less, it is easy to form voids for obtaining sufficient lightness and cushioning properties.
[0065] As the inorganic pigment contained in the first coating layer B1 and the second coating layer B2, silicon dioxide, kaolinite, talc, calcium carbonate, zeolite, aluminum oxide, barium sulfate, titanium oxide, zinc sulfide, etc. can be listed. Among these, from the viewpoint of concealment and whiteness, titanium oxide, calcium carbonate, barium sulfate, and particularly titanium oxide are preferred. In addition, these inorganic pigments can be used alone or in combination of two or more. These pigments can be present in the film by being added to the polyester resin in advance.
[0066] The amount of the inorganic pigment added to the first covering layer B1 is not particularly limited, but is preferably 1% by mass or more and 35% by mass or less, and more preferably 2% by mass or more and 30% by mass or less, relative to 100% by mass of all the components constituting the first covering layer B1. When the amount of the inorganic pigment added is 1% by mass or more and 35% by mass or less, it is easy to improve the concealment and whiteness of the polyester-based easy-adhesive film containing voids, and it is possible to improve the film-forming properties and mechanical strength of the polyester-based easy-adhesive film containing voids.
[0067] The amount of inorganic pigment added in the second covering layer B2 is not particularly limited, and is preferably the same as the amount of inorganic pigment added in the first covering layer B1. The first covering layer B1 and the second covering layer B2 are also preferably substantially the same in composition, thickness, etc. That is, the stacked structure of the first covering layer B1 / void-containing layer A / second covering layer B2 is also preferably a 2-type 3-layer structure. In addition, it is preferred that a functional easy-adhesion layer is stacked on the first covering layer B1, and it is also preferred that a functional easy-adhesion layer that is the same as the functional easy-adhesion layer on the first covering layer B1 or different in composition, thickness, etc. is stacked on the second covering layer B2.
[0068] The inorganic pigment contained in the first coating layer B1 and the second coating layer B2 is preferably in a granular form, and the average particle size of the particles is preferably 0.1 to 4.0 μm, and particularly preferably 0.3 to 1.5 μm. Specifically, granular white pigments such as titanium oxide, barium sulfate, calcium carbonate, and zinc sulfide are preferred, and they may be mixed. Furthermore, inorganic particles commonly contained in thin films, such as silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, and calcium sulfate may be used in combination.
[0069] The shape of the particles is not particularly limited as long as the purpose of the present invention is achieved, and spherical particles and irregular non-spherical particles can be used. The particle size of the irregular particles can be calculated as a circle equivalent diameter.
[0070] In addition, in order to improve the coating and adhesion of printing ink, coating agent, etc., the void-containing polyester-based easy-adhesive film of the present invention is preferably provided with a functional easy-adhesive layer having both easy adhesion and antistatic properties on at least one side thereof. As the resin contained in the composition constituting the functional easy-adhesive layer, polyester resin, urethane resin having a polycarbonate structure, polyester urethane resin, acrylic resin, etc., which are generally disclosed as means for improving the adhesion of polyester-based films, can be applied. In order to facilitate so-called in-line coating, the resin is preferably water-soluble and water-dispersible.
[0071] In the present invention, a blocked isocyanate as a crosslinking agent may be added to the composition constituting the functional easy-adhesive layer. A blocked isocyanate having three or more functions is more preferred, and a blocked isocyanate having four or more functions is particularly preferred. Thus, the antistatic property of the surface of the easy-adhesive layer when an antistatic agent is included in the composition described later can be controlled and the back transfer property of the antistatic agent can be suppressed.
[0072] Regarding the blocked isocyanate in the present invention, in order to impart water solubility or water dispersibility, a hydrophilic group can be introduced into the polyisocyanate as a precursor. Examples of the hydrophilic group include: (1) quaternary ammonium salts of dialkylamino alcohols, quaternary ammonium salts of dialkylaminoalkylamines, etc.; (2) sulfonates, carboxylates, phosphates, etc.; (3) polyethylene glycol and polypropylene glycol, etc., which are terminated at a single end with an alkyl group. When a hydrophilic portion is introduced, (1) cationic, (2) anionic, and (3) nonionic properties are exhibited. Among them, other water-soluble resins are mostly anionic, and therefore, anionic and nonionic properties that are easily compatible are preferred. In addition, anionic properties have excellent compatibility with other resins, and nonionic properties do not have ionic hydrophilic groups, and therefore, are also preferred for improving moisture-heat resistance.
[0073] As the anionic hydrophilic group, a hydroxyl group for introducing into the polyisocyanate or a carboxylic acid group for imparting hydrophilicity is preferred. Examples thereof include glycolic acid, lactic acid, tartaric acid, citric acid, hydroxybutyric acid, hydroxyvaleric acid, hydroxypivalic acid, dimethylolacetic acid, dimethylolpropionic acid, dimethylolbutyric acid, and polycaprolactone having a carboxylic acid group. In order to neutralize the carboxylic acid group, an organic amine compound is preferred. Examples thereof include straight-chain or branched primary, secondary or tertiary amines having 1 to 20 carbon atoms, such as ammonia, methylamine, ethylamine, propylamine, isopropylamine, butylamine, 2-ethylhexylamine, cyclohexylamine, dimethylamine, diethylamine, dipropylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine and ethylenediamine; cyclic amines such as morpholine, N-alkylmorpholine and pyridine; and amines containing hydroxyl groups, such as monoisopropanolamine, methylethanolamine, methylisopropanolamine, dimethylethanolamine, diisopropanolamine, diethanolamine, triethanolamine, diethylethanolamine and triethanolamine.
[0074] As a nonionic hydrophilic group, the repeating units of ethylene oxide and / or propylene oxide of polyethylene glycol and polypropylene glycol that are single-terminated with an alkyl group are preferably 3 to 50, and more preferably 5 to 30. When the repeating unit is small, the compatibility with the resin sometimes deteriorates and the haze increases. When the repeating unit is large, the adhesion under high temperature and high humidity sometimes decreases. In order to improve the water dispersibility, nonionic, anionic, cationic, and amphoteric surfactants can be added to the blocked isocyanate of the present invention. Examples include nonionic surfactants such as polyethylene glycol and polyol fatty acid esters; anionic surfactants such as fatty acid salts, alkyl sulfates, alkylbenzene sulfonates, sulfosuccinates, and alkyl phosphates; cationic surfactants such as alkylamine salts and alkyl betaines; surfactants such as carboxylic acid amine salts, sulfonic acid amine salts, and sulfate ester salts.
[0075] It is preferred to add an antistatic agent to the composition constituting the functional easy-adhesive layer. The antistatic agent is preferably capable of inhibiting the transferability to other contacted articles or the back side of the film itself. For example, the functional group can include nonionic systems such as sorbitan type, ether type, ester type, sorbitol type, glucose type, quaternary ammonium salt type, quaternary ammonium resin type, imidazoline type, Arcobel type, Soromine A type, etc.; anionic systems such as alkyl sulfate type, alkyl phosphate type, phosphate ester salt type, sulfate ester salt type; and amphoteric surfactant types or polymer types such as betaine type, amino acid type, aminosulfate type, etc.
[0076] In the above antistatic agent, the counter ion of the quaternary ammonium salt is not particularly limited as long as it is an anionic compound, and can be preferably appropriately selected from halogen ions, monohalogenated alkyl ions or polyhalogenated alkyl ions, nitrate ions, sulfate ions, alkyl sulfate ions, sulfonate ions or alkyl sulfonate ions. Preferably, ethyl sulfate is preferably used for the stability of the surface resistivity value, the coating liquid stability, the ink adhesion, and the transferability of the antistatic agent to other articles and the back side.
[0077] (Polycarbonate urethane resin)
[0078] In the present invention, the urethane resin having a polycarbonate structure preferably contained in the composition constituting the functional easy-adhesion layer preferably has at least a urethane bonding partial structure derived from a polycarbonate polyol component and a polyisocyanate component, and further contains a chain extender as required. It is preferred that the polyisocyanate having a branched structure is suitably introduced by allowing the terminal functional groups of any of the above-mentioned raw material components constituting the molecular chain to exist at least 3 so as to form a molecular chain structure on a branch after synthesis and polymerization.
[0079] For the carbamate resin having a polycarbonate structure in the present invention and having a branched structure, the lower limit of the number of terminal functional groups in the molecular chain is preferably 3, and more preferably 4, depending on the branched structure. If it is 3 or more, the anti-blocking property during water adhesion can be improved, so it is preferred. For the carbamate resin having a polycarbonate structure in the present invention, the upper limit of the number of terminal functional groups in the molecular chain is preferably 6, depending on the branched structure. If it is 6 or less, the resin can be stably dispersed in an aqueous solution, so it is preferred.
[0080] The polycarbonate polyol component used for polymerizing the urethane resin having a polycarbonate structure in the present invention preferably contains an aliphatic polycarbonate polyol having excellent heat resistance and hydrolysis resistance. Examples of the aliphatic polycarbonate polyol include aliphatic polycarbonate diols and aliphatic polycarbonate triols, and aliphatic polycarbonate diols can be suitably used. Examples of the aliphatic polycarbonate diol used for polymerizing the urethane resin having a polycarbonate structure in the present invention include aliphatic polycarbonate diols obtained by reacting one or more of diols such as ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 1,8-nonanediol, neopentyl glycol, diethylene glycol, and dipropylene glycol with carbonates such as dimethyl carbonate, ethylene carbonate, and phosgene.
[0081] The functional adhesive layer may contain lubricant particles in order to impart slidability, matte properties, ink absorbency, etc. to the surface. The particles may be inorganic particles or organic particles, and are not particularly limited. Examples thereof include: (1) inorganic particles such as silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, zirconium oxide, titanium dioxide, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, calcium carbonate, magnesium carbonate, calcium phosphate, magnesium hydroxide, and barium sulfate; and (2) organic particles such as acrylic or methacrylic, vinyl chloride, vinyl acetate, nylon, styrene / acrylic, styrene / butadiene, polystyrene / acrylic, polystyrene / isoprene, polystyrene / isoprene, methyl methacrylate / butyl methacrylate, melamine, polycarbonate, urea, epoxy, urethane, phenol, diallyl phthalate, and polyester. In order to impart appropriate slip properties to the easy-adhesion layer, silica is particularly preferably used.
[0082] The average particle size of the particles is preferably 0.1 to 2.4 μm, more preferably 0.3 to 2.0 μm. If the average particle size of the particles is 0.1 μm or less, the glossiness of the film surface may increase. On the contrary, if it exceeds 2.4 μm, the particles tend to fall off from the functional easy-adhesion layer and cause powder loss.
[0083] The content of the aforementioned particles can be added within a range that does not hinder the effect of the present invention. In order to prevent the particles from falling off from the functional easy-adhesive layer and causing powdering, the solid content of the particles is preferably 0 to 70.0% by mass, preferably 0 to 60.0% by mass, and more preferably 0 to 55.0% by mass, relative to the overall solid content of the functional easy-adhesive layer.
[0084] The shape of the particles is not particularly limited as long as the purpose of the present invention is achieved, and spherical particles and irregular non-spherical particles can be used. The particle size of the irregular particles can be calculated as a circle equivalent diameter.
[0085] (Polyester resin)
[0086] The polyester resin preferably included in the composition forming the functional easy-adhesion layer in the present invention may be linear, and more preferably, a polyester resin preferably having dicarboxylic acid and diol having a branched structure as constituent components. The dicarboxylic acid mentioned here includes aliphatic dicarboxylic acids such as adipic acid and sebacic acid, and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalene dicarboxylic acid, in addition to terephthalic acid, isophthalic acid, orthophthalic acid, and 2,6-naphthalene dicarboxylic acid. The branched diol refers to a diol having a branched alkyl group, and examples thereof include 2,2-dimethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-2-butyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-methyl-2-isopropyl-1,3-propanediol, 2-methyl-2-n-hexyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-ethyl-2-n-butyl-1,3-propanediol, 2-ethyl-2-n-hexyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 2-n-butyl-2-propyl-1,3-propanediol, and 2,2-di-n-hexyl-1,3-propanediol.
[0087] In the above-mentioned polyester resin, it can be said that the diol component of the branched chain as the above-mentioned more preferred mode is preferably contained in a ratio of 10 mol% or more, more preferably in a ratio of 20 mol% or more among all diol components. If it is 10 mol% or more, the crystallinity will not become too high, and the adhesion of the easy-adhesive layer becomes good, so it is preferred. The upper limit of the diol component in all diol components is preferably 80 mol% or less, more preferably 70 mass%. If it is 80 mol% or less, the oligomer concentration as a by-product is suppressed, and the transparency of the easy-adhesive layer is good, so it is preferred. As a diol component other than the above-mentioned compound, ethylene glycol is most preferably used. If it is a small amount, diethylene glycol, propylene glycol, butanediol, hexanediol or 1,4-cyclohexanedimethanol can be used.
[0088] As for the dicarboxylic acid as a constituent component of the polyester resin, terephthalic acid or isophthalic acid is most preferred. In addition to the above dicarboxylic acids, in order to impart water dispersibility to the copolymerized polyester resin, it is preferred to copolymerize 5-sulfoisophthalic acid in a numerical range of 1 to 10 mol%, for example, dimethyl 5-sulfoisophthalate, etc. A polyester resin containing a dicarboxylic acid having a naphthalene skeleton may be used, but in order to suppress the decrease in adhesion to UV ink, the amount thereof is preferably less than 5 mol% in the total carboxylic acid components, and it may not be used.
[0089] The polyester resin may contain a triol or a tricarboxylic acid as a constituent component to such an extent that the characteristics as the polyester resin are not impaired.
[0090] The polyester resin may contain polar groups other than carboxyl groups. Examples include sulfonic acid metal salt groups, phosphoric acid groups, etc., which may have one or more types. As a method for introducing sulfonic acid metal salt groups, a method of using metal salts of 5-sulfoisophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5-〔4-sulfophenoxy〕isophthalic acid, etc. or metal salts of 2-sulfo-1,4-butanediol, 2,5-dimethyl-3-sulfo-2,5-hexanediol, etc., containing dicarboxylic acids or diols of sulfonic acid metal salt groups can be cited within a range of less than 10 mol %, preferably less than 7 mol %, and more preferably less than 5 mol % of the total of the polycarboxylic acid component or the polyol component. If it exceeds 10 mol %, there is a tendency for the hydrolysis resistance of the resin itself and the water resistance of the coating film to decrease.
[0091] As the means to improve the close adhesion, other disclosed compounds can be applied to add.In order to improve the close adhesion durability of the functional easy-adhesive layer, even other cross-linking agents can further improve the close adhesion under the high temperature and humidity.As specific cross-linking agent, urea system, epoxy system, melamine system, oxazoline system, carbodiimide system etc. can be listed.In addition, in order to promote the cross-linking reaction, catalyst etc. can be suitably used as required.
[0092] (additive)
[0093] The functional easy-adhesion layer in the present invention may contain known additives such as surfactants, pH adjusters, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic particles, nucleating agents, etc., within a range that does not hinder the effects of the present invention.
[0094] As a method for providing a functional easy-adhesive layer, commonly used methods such as gravure coating, kiss coating, dipping, spraying, curtain coating, air knife coating, blade coating, reverse roll coating, etc. can be applied. As the stage of coating, any method such as a method of coating before stretching the film, a method of coating after longitudinal stretching, and a method of coating on the surface of the film after the stretching treatment is completed can be applied.
[0095] The method for producing the void-containing polyester-based easy-adhesive film of the present invention is described below. For example, after drying a mixed pellet composed of a composition containing a polyester resin, a polypropylene resin and a silicone resin, the mixed pellet is melt-extruded from a T-shaped nozzle into a sheet, and the sheet is made to adhere to a casting drum by an electrostatic application method or the like and cooled and solidified to obtain an unstretched film.
[0096] Next, the unstretched film is stretched / oriented. The most commonly used sequential biaxial stretching method, especially the method of longitudinally stretching the unstretched film along the length direction and then transversely stretching it along the width direction, is described below as an example. First, in the longitudinal stretching process along the length direction, the film is heated and stretched to 2.5 to 5.0 times between two or more rollers with different peripheral speeds. The heating means at this time may be a method using a heated roller or a method using a non-contact heating medium, or a combination of these. At this time, it is preferred to set the temperature of the film to the range of (Tg-10°C) to (Tg+50°C). Next, the uniaxially stretched film is coated with a reverse gravure coating method with a WET coating amount of 1 to 20 g / m 2 After coating in a manner of , it is introduced into a tenter and stretched to 2.5 to 5 times in the width direction at a temperature of (Tg-10°C) to Tm-10°C or less, thereby obtaining a biaxially stretched film.
[0097] Here, Tg is the glass transition temperature of the polyester resin, and Tm is the melting point of the polyester. The film obtained as described above is preferably subjected to heat treatment as necessary, and the treatment temperature is preferably within the range of (Tm-60°C) to Tm.
[0098] In addition, the void-containing polyester-based adhesive film of the present invention may also contain recycled raw materials formed from the used void-containing polyester-based adhesive film of the present invention in the void-containing layer A. The used void-containing polyester-based adhesive film of the present invention refers to: the edge portion generated in the film-making process, the scrap film generated due to the fracture failure, etc., and the film recovered from the market. In the case of adding recycled raw materials to the void-containing layer A, if the recycled raw materials of the void-containing polyester-based adhesive film of the present invention are used, a small amount of silicone resin is added to the polypropylene resin, so that the void visualization can be maintained. As a result, the void-containing polyester-based adhesive film can obtain sufficient lightness and cushioning properties, and can obtain a void-containing polyester-based adhesive film with excellent concealment and whiteness. Especially at the moment when it is required to cope with the environmental burden, the amount of recycled raw materials added is increased compared with the past because the used void-containing polyester-based adhesive film is reused. However, if a silicone resin is added, the void visualization can be maintained even when the amount added is increased.
[0099] The amount of the recycled raw material added is preferably 5 to 70% by mass relative to 100% by mass of the total mass of the void-containing layer A from the viewpoint of raw material cost reduction, whiteness, and film forming properties.
[0100] The first covering layer B1 or the second covering layer B2 may contain recycled materials, but preferably contain no recycled materials from the viewpoint of deterioration of whiteness and exposure of polypropylene resin in the recycled materials.
[0101] The apparent density of the void-containing polyester-based adhesive film of the present invention is preferably 0.80 g / cm 3 Above and 1.2g / cm 3 Below, more preferably 0.80g / cm 3 Above and 1.10g / cm 3 Below. The apparent density is 0.80g / cm 3 Above and 1.20g / cm 3 In the following cases, the total voids in the void-containing polyester-based easy-adhesive film become appropriate, and it is easy to handle during post-processing such as printing processing and during use. 3 Above and 1.20g / cm 3 In the following cases, sufficient lightness and cushioning properties can be obtained.
[0102] In particular, the void-containing polyester-based easy-adhesive film of the present invention has excellent lightness, film-forming properties, hiding properties, and whiteness even if the apparent density is 0.80 to 1.10 by containing a trace amount of silicone resin.
[0103] In addition, the apparent density is a value obtained by the measuring method described in the evaluation method mentioned later.
[0104] The total light transmittance of the void-containing polyester-based easy-adhesive film of the present invention is preferably 30% or less, more preferably 25% or less. When the total light transmittance is 30% or less, sufficient concealment can be obtained. For example, when used for labels, the image printed on the label becomes clear. It should be noted that the total light transmittance is a value converted to a thickness of 50 μm obtained by the measurement method described in the evaluation method described later.
[0105] The color tone b value of the void-containing polyester-based easy-adhesive film of the present invention is preferably 4.0 or less, more preferably 3.0 or less, and particularly preferably 1.5 or less. When the color tone b value is greater than 4.0, the whiteness is poor, and when it is made into a label, etc., there is a concern that the clarity during printing is reduced and the product value is damaged.
[0106] The thickness of the void-containing polyester-based easy-adhesive film of the present invention is arbitrary, but is preferably 20 μm or more and 300 μm or less.
[0107] In the present invention, the remaining area of the functional adhesive layer in close contact with the curable ink printed layer obtained by the evaluation method described below is preferably 90% or more of the entirety, more preferably 99% or more, and most preferably 100%.
[0108] As described above, the functional easy-adhesion layer preferably contains an antistatic agent, and the surface resistivity value is preferably 1.0×10 13 Ω / sq or less. More preferably, 1.0×10 12 Ω / sq or less, particularly preferably 1.0×10 11 Ω / sq or less. The lower limit is not particularly limited, but is preferably 1.0×10 5 Ω / sq or more, preferably 1.0×10 6 Ω / sq or more.
[0109] The number of pinhole-like shrinkage holes in the functional adhesive layer obtained by the evaluation method described below is preferably 5 pieces / m 2 The smaller the number of pinhole-like shrinkage holes, the better. Of course, the most preferred number is 0 / m 2 .
[0110] The functional easy-adhesive layer of the polyester-based easy-adhesive film containing voids of the present invention preferably has a water contact angle of 50 to 90° after heating at 150°C for 30 minutes. More preferably, it is 55 to 85°. When the water contact angle is 90° or less, the polyester-based easy-adhesive film containing voids can suppress the coating and printing from falling off during the processing step. The water contact angle is preferably small, and when containing a polyester resin, it is also preferably 50° or more. In addition, the contact angle of diiodomethane of the functional easy-adhesive layer after heating at 150°C for 30 minutes is preferably 10 to 60°. When the contact angle of diiodomethane is 60° or less, the polyester-based easy-adhesive film containing voids can suppress the coating and printing from falling off during the processing step. When the contact angle of diiodomethane is 10° or more, the polyester-based easy-adhesive film containing voids can improve the adhesion between the coating and the original material in the processing step.
[0111] The functional easy-adhesive layer of the polyester-based easy-adhesive film containing voids of the present invention preferably has a water contact angle of 46 to 90° at 85°, 85% RH, and 72 hours. More preferably, it is 50 to 85°. When the water contact angle is 90° or less, the polyester-based easy-adhesive film containing voids can suppress the coating from falling off and the printing from falling off during processing after being stored in a warehouse for a long time. The water contact angle is preferably small, but in the case of containing a polyester resin, it is preferred to be 46° or more. In addition, the contact angle of diiodomethane of the functional easy-adhesive layer at 85°, 85% RH, and 72 hours is preferably 10 to 60°. When the contact angle of diiodomethane is 60° or less, the polyester-based easy-adhesive film containing voids can suppress the coating from falling off and the printing from falling off during processing after being stored in a warehouse for a long time. When the contact angle of diiodomethane is 10° or more, the polyester-based easy-adhesive film containing voids can improve the adhesion between the coating and the raw material in the processing step.
[0112] In summary, in the void-containing polyester-based easy-adhesive film of the present invention, by making the void-containing layer A contain a trace amount of silicone resin, it is possible to suppress the thermal degradation of the polypropylene resin during, for example, the processing step, and to maintain the void visibility. Therefore, the void-containing polyester-based easy-adhesive film of the present invention has excellent lightness, film-forming properties, concealing properties, and whiteness even if the apparent density is 0.80 to 1.20.
[0113] Therefore, the void-containing polyester-based easy-adhesive film of the present invention is suitable for use as a substrate such as labels, cards, packaging materials, and release films used in the production of polarizing plates or laminated ceramic capacitors.
[0114] Example
[0115] The present invention is specifically described below with reference to the following examples. It should be noted that the present invention is not limited to the following examples. It should be noted that each evaluation item in the examples and comparative examples was measured by the following method.
[0116] (1) Film-forming properties
[0117] The film was evaluated as follows based on the number of breakages during production with a film production time of 2 hours under the film production conditions described in the later-described production of a void-containing polyester-based easy-adhesive film.
[0118] ○: Not broken
[0119] △: Broken 1 to 3 times
[0120] ×: Broken more than 4 times, unable to form film
[0121] (2) Apparent density
[0122] Cut the void-containing polyester easy-adhesive film into 4 square pieces of 5.0 cm square, overlap the 4 pieces, use a micrometer to change the total thickness position to 4 significant figures to measure 10 points, and find the average thickness of the 4 overlapping pieces. Divide the average value by 4, round it to 3 significant figures, and use it as the average thickness of each piece (t: μm). Use an automatic dish balance to measure the mass (w: g) of the 4 samples to 4 significant figures, and find the apparent density by the following formula. It should be noted that the apparent density is rounded to 3 significant figures.
[0123] Apparent density (g / cm 3 ) = w / (5.0×5.0×t×10 -4 ×4)
[0124] (3) Total light transmittance
[0125] The haze was measured using a haze meter (NDH5000 manufactured by Nippon Denshoku Industries Co., Ltd.) and converted into a value per 50 μm of film thickness. The same measurement was performed three times, and the arithmetic mean value was used.
[0126] (4) Hue b value
[0127] The color tone b value is measured using a colorimeter (ZE6000) manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS-8722. The smaller the color tone b value is, the higher the whiteness is and the weaker the yellowness is.
[0128] (5) Water contact angle after heating at 150°C for 30 minutes
[0129] After heating the sample in a gear oven at 150° for 30 minutes, the contact angle with distilled water was measured using a FACE contact angle meter (CA-X model, manufactured by Kyowa Interface Chemical Co., Ltd.) after being dropped onto the surface of the functional easy-adhesion layer for 1 minute. It should be noted that 5 measurements were performed for each sample, and the average of the 3 measured values after removing the maximum and minimum values of the measured values was taken as the contact angle.
[0130] (6) Diiodomethane contact angle after heating at 150°C for 30 minutes
[0131] After heating the sample in a gear oven at 150° for 30 minutes, the contact angle with diiodomethane was measured using a FACE contact angle meter (manufactured by Kyowa Interface Chemical Co., Ltd., CA-X model) after being dropped onto the surface of the functional easy-adhesion layer for 1 minute. It should be noted that 5 measurements were performed for each sample, and the average of the 3 measured values after removing the maximum and minimum values of the measured values was taken as the contact angle.
[0132] (7) Water contact angle at 85°C, 85% RH, 72 hours
[0133] After the sample was placed in a constant temperature and humidity machine at 85°C and 85% RH for 72 hours, the contact angle with distilled water was measured using a FACE contact angle meter (manufactured by Kyowa Interface Chemical Co., Ltd., CA-X model) after being dropped onto the surface of the functional easy-adhesion layer for 1 minute. It should be noted that 5 measurements were performed for each sample, and the average of the 3 measured values after removing the maximum and minimum values of the measured values was taken as the contact angle.
[0134] (8) Diiodomethane contact angle after 72 hours at 85°C and 85% RH
[0135] After the sample was placed in a constant temperature and humidity machine at 85°C and 85% RH for 72 hours, the contact angle with diiodomethane was measured 1 minute after it was dropped onto the surface of the functional easy-adhesion layer using a FACE contact angle meter (manufactured by Kyowa Interface Chemical Co., Ltd., CA-X model). It should be noted that 5 measurements were performed for each sample, and the average of the 3 measured values after removing the maximum and minimum values of the measured values was taken as the contact angle.
[0136] (9) Determination of polydimethylsiloxane content
[0137] After dissolving in 0.1 ml of CDCl3 (deuterated chloroform) / HFIP-d (deuterated hexafluoroisopropanol) (volume ratio of 1 / 1), add 0.5 ml of TCE (tetrachloroethane)-d and dissolve at 130°C. The solution is subjected to H-NMR measurement at 120°C, and the mass ratio of polydimethylsiloxane is calculated based on the ratio of the integral values of the obtained components. The peak of polydimethylsiloxane is the peak detected near 0.2 ppm of the NMR spectrum. The content of polydimethylsiloxane in the void-containing layer A is calculated using the layer ratio. Since the silicone resin is cross-linked and has a lot of insoluble components, it is difficult to quantify the amount of addition, but if the above method is used, the soluble component of polydimethylsiloxane in the silicone resin can be quantified. It can be confirmed that there is a correlation between the amount of silicone resin added and the content of polydimethylsiloxane.
[0138] (10) Determination of the mass ratio of polypropylene resin content to polydimethylsiloxane content
[0139] H-NMR measurement was carried out in the same manner as above, and the mass ratio was calculated from the ratio of the integrated values of the peaks of the polypropylene resin and the polydimethylsiloxane in the obtained NMR spectrum.
[0140] (11) Adhesion with UV ink
[0141] The functional easy-adhesive layer of the polyester-based easy-adhesive film containing voids was printed using UV ink [T&K TOKA Co., Ltd., trade name "BEST CURE (registered trademark) UV161 Blue S"] using a printer [Ming Manufacturing Co., Ltd., trade name "RI TESTER"], and then the film coated with the ink layer was irradiated with 40 mJ / cm using a high-pressure mercury lamp. 2 The ultraviolet light of the UV curing ink was cured. Next, a cellophane adhesive tape (CT405AP-24) manufactured by NICHIBAN was cut into 24 mm wide and 50 mm long, and was completely attached using a hand-held rubber roller in a manner that prevented air from mixing into the surface of the ink layer. Afterwards, the cellophane adhesive tape was peeled off vertically, and the remaining area of the printed layer was observed in an area of 24 mm × 50 mm, and judged according to the following criteria.
[0142] ○: The remaining area of the printed layer is more than 99% of the total
[0143] △: The remaining area of the printed layer is more than 90% and less than 99% of the total
[0144] ×: The remaining area of the printed layer is less than 90% of the total
[0145] In the present invention, 90% or more was regarded as acceptable.
[0146] (12) Antistatic property (surface resistivity)
[0147] The void-containing polyester easy-adhesive film was cut into three square pieces of 5.00 cm square as a sample. The surface resistivity was measured using a surface resistivity measuring instrument (Hiresta MCP-HT800 manufactured by Nittoseiko Analytech Co., Ltd.) under the conditions of an applied voltage of 500 V, 23° C. and 65% humidity, and the surface resistivity values of three pieces were measured in accordance with JIS K6911 and the average value was obtained.
[0148] (13) Appearance shrinkage hole determination
[0149] Ten rectangular films of a polyester-based adhesive film containing voids were randomly cut out, with a length direction (also called longitudinal direction or machine direction) of 300 mm and a width direction of 210 mm. The number of pinhole-like shrinkage holes in the functional adhesive layer was counted by visual observation under a three-wavelength LED light and converted into a density per 1 m. 2 to make an evaluation.
[0150] 0:Every 1m 2 The number of pinhole-like shrinkage holes in the film is 0 or more and 5 or less
[0151] △: Every 1m 2The number of pinhole-like shrinkage holes in the film is 6 or more and 10 or less
[0152] ×: Every 1m 2 The number of pinhole-like shrinkage holes in the film exceeds 10
[0153] In the present invention, 5 or less samples were considered acceptable.
[0154] (Example 1)
[0155] [Manufacture of Titanium Oxide Masterbatch Pellets (M1)]
[0156] 50% by mass of anatase-type titanium dioxide having an average particle size of 0.3 μm (by electrochemical method) was mixed with 50% by mass of polyethylene terephthalate resin having an intrinsic viscosity of 0.62, and the mixture was supplied to a vented twin-screw extruder and kneaded to produce master batch pellets (M1) containing titanium oxide.
[0157] [Manufacturing of Silicone Resin S]
[0158] A thermosetting silicone resin (KS-774 manufactured by Shin-Etsu Chemical Co., Ltd.) was diluted with a solvent, and 3 parts by mass of a catalyst (CAT-PL-3 manufactured by Shin-Etsu Chemical Co., Ltd.) was added to 100 parts by mass of the silicone resin, and heated at 150° C. for 60 seconds. After the heating, the cured silicone resin was powdered to obtain a silicone resin S.
[0159] [Manufacturing of unstretched film]
[0160] 93% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62, 6.92% by mass of polypropylene resin with MFR=2.5, Mw=320000, Mw / Mn=4.0, and load deflection temperature=92°C, and 800ppm of silicone resin S are mixed. The mixture is vacuum dried to prepare a raw material for the void-containing layer A. On the other hand, 30% by mass of the masterbatch pellets (M1) containing titanium oxide are pelletized with 70% by mass of polyethylene terephthalate resin with an intrinsic viscosity of 0.62. The mixture is vacuum dried to prepare a raw material for the first covering layer B1 and the second covering layer B2. These raw materials are supplied to their respective extruders, melted at 285°C, and the void-containing layer A, the first covering layer B1, and the second covering layer B2 are stacked in the order of B1 / A / B2. The laminate was joined by a feed block so that the thickness ratio was 10 / 80 / 10. The joined body was extruded from a T-die onto a cooling drum adjusted to 30° C. to produce two types of three-layered unstretched films.
[0161] [Functional adhesive layer]
[0162] (Cationic antistatic agent A)
[0163] Using 116 g of N,N-dimethyl-1,3-propanediamine and 285 g of stearic acid having 17 carbon atoms, an esterification reaction was carried out at 100° C. in a nitrogen atmosphere for 10 hours, tetrahydrofuran was added as a quaternization solvent, a predetermined amount of dimethylsulfuric acid was added to the target amine, and the reaction was carried out at 70° C. for about 10 hours. After the reaction, the solvent was distilled off under reduced pressure, and isopropanol was added to adjust to a desired solid content concentration, thereby obtaining an isopropanol solution of a cationic antistatic agent A having quaternary ammonium ethylsulfate.
[0164] (Polymerization of Urethane Resin B Having Polycarbonate Structure)
[0165] In a four-necked flask equipped with a stirrer, a Dimrot condenser, a nitrogen inlet tube, a silica gel drying tube and a thermometer, 22 parts by mass of 4,4-dicyclohexylmethane diisocyanate, 20 parts by mass of polyethylene glycol monomethyl ether with a number average molecular weight of 700, 53 parts by mass of polyhexamethylene carbonate diol with a number average molecular weight of 2100, 5 parts by mass of neopentyl glycol and 84.00 parts by mass of acetone as a solvent were added, and stirred at 75°C for 3 hours under a nitrogen atmosphere to confirm that the reaction liquid reached the specified amine equivalent. Next, 16 parts by mass of a polyisocyanate compound having an isocyanurate structure (manufactured by Asahi Kasei Chemicals Co., Ltd., DURANATE (registered trademark) TPA, trifunctional) with hexamethylene diisocyanate as a raw material was added, and stirred at 75°C for 1 hour under a nitrogen atmosphere to confirm that the reaction liquid reached the specified amine equivalent. Thereafter, the temperature of the reaction liquid was lowered to 50°C, and 7 parts by mass of methyl ethyl ketoxime was added dropwise. The reaction solution was cooled to 40°C to obtain a polyurethane prepolymer solution. Next, 450 g of water was added to a reaction vessel equipped with a homodispersor capable of high-speed stirring, and the temperature was adjusted to 25°C. The mixture was stirred for 2000 min. -1 The polyurethane prepolymer solution was added while stirring and mixing to perform water dispersion. Thereafter, a portion of acetone and water was removed under reduced pressure to prepare a solution having a solid content of water-dispersible urethane resin B of 35% by mass.
[0166] (Polymerization of Blocked Isocyanate Crosslinking Agent C)
[0167] Into a flask equipped with a stirrer, a thermometer, and a reflux condenser, 100 parts by mass of a polyisocyanate compound having an isocyanurate structure (manufactured by Asahi Kasei Chemicals Co., Ltd., DURANATE (registered trademark) TPA) with hexamethylene diisocyanate as a raw material, 55 parts by mass of propylene glycol monomethyl ether acetate, and 30 parts by mass of polyethylene glycol monomethyl ether (average molecular weight of 750) were added, and kept at 70°C for 4 hours under a nitrogen atmosphere. Thereafter, the temperature of the reaction liquid was lowered to 50°C, and 47 parts by mass of methyl ethyl ketone oxime was added dropwise. The infrared spectrum of the reaction liquid was measured to confirm that the absorption of the isocyanate group had disappeared, and 210 parts by mass of water were added to obtain an aqueous dispersion of an oxime-blocked isocyanate crosslinker (C) having a solid content of 40% by mass. The number of functional groups of the blocked isocyanate crosslinker is 3 and the NCO equivalent is 170.
[0168] (Polymerization of Copolyester Resin D-1)
[0169] 194.2 parts by mass of dimethyl terephthalate, 184.5 parts by mass of dimethyl isophthalate, 14.8 parts by mass of dimethyl 5-sulfonate sodium isophthalate, 185 parts by mass of neopentyl glycol, 188 parts by mass of ethylene glycol and 0.2 parts by mass of tetra-n-butyl titanate were added to a stainless steel autoclave equipped with a stirrer, a thermometer and a partial reflux condenser, and an ester exchange reaction was carried out at a temperature of 160°C to 220°C for 4 hours. Then, the temperature was raised to 255°C, and the reaction system was slowly decompressed, and then reacted for 1 hour and 30 minutes under a reduced pressure of 30 Pa to obtain a copolyester resin (D-1). The obtained copolyester resin (D-1) was light yellow and transparent. The result of measuring the reduced viscosity of the copolyester resin (D-1) was 0.40 dl / g. The glass transition temperature based on DSC was 65°C.
[0170] (Preparation of Polyester Aqueous Dispersion Dw-1)
[0171] 25 parts by mass of the copolyester resin (D-1) and 10 parts by mass of ethylene glycol mono-n-butyl ether were added to a reactor equipped with a stirrer, a thermometer and a reflux device, and the resin was dissolved by heating and stirring at 110°C. After the resin was completely dissolved, 65 parts by mass of water were slowly added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to prepare a milky white polyester aqueous dispersion (Dw-1) having a solid content of 25% by mass.
[0172] (Example 1)
[0173] The solid content in the coating liquid of the coating compound constituting the functional easy-adhesion layer is as follows.
[0174] The total of the solid content contained in the functional easily-adhesive layer is set to 100 mass %.
[0175] Cationic antistatic agent A: 6.2 mass%
[0176] Urethane resin B having a polycarbonate structure: 22.8% by mass
[0177] Blocked isocyanate crosslinking agent C: 10.9 mass%
[0178] ·Polyester resin Dw-1: 54.6 mass%
[0179] Silicone surfactant: 0.4% by mass
[0180] pH adjuster (sodium bicarbonate): 2.4 mass%
[0181] The solid content mass ratio of urethane resin (B) / crosslinking agent (C) / polyester resin (Dw-1) was 28 / 12 / 60.
[0182] [Production of polyester-based easy-to-bond films containing voids]
[0183] A polyester-based easy-to-adhesive film containing voids is produced under the following film-making conditions. That is, the obtained unstretched film is uniformly heated to 70°C using a heating roller, and longitudinally stretched to 3.4 times between two pairs of clamping rollers with different peripheral speeds. At this time, as an auxiliary heating device for the unstretched film, an infrared heating heater (rated value: 20W / cm) with a gold reflective film in the middle of the clamping roller is set opposite to both sides of the film (at a distance of 1 cm from the film surface) and heated. On one side of the uniaxially stretched film obtained by the above-mentioned coating structure, the reverse gravure coating method is used to coat the film with a WET coating amount of 7g / m 2 After coating in the manner of , it was introduced into a tenter, heated to 140°C, stretched to 4.0 times in the transverse direction, fixed in width, heat treated at 235°C, and then relaxed by 3% in the width direction at 210°C, thereby obtaining a film with a thickness of 50 μm and a functional easy-adhesive layer with a thickness of 0.11 g / m 2 The results of apparent density, water contact angle, diiodomethane contact angle, color tone b value, total light transmittance and film forming properties are shown in Table 1. It should be noted that the gloss value of the surface of the functional easy-adhesive layer under 60-degree regular reflection is 70%, which is a functional easy-adhesive layer with excellent gloss.
[0184] (Examples 2, 3, 5)
[0185] In Example 1, except that the raw material ratio of the void-containing layer A was changed as shown in Table 1, the same method as in Example 1 was used to obtain a void-containing polyester-based easy-adhesion film.
[0186] (Example 4)
[0187] In Example 1, a void-containing polyester-based adhesive film was obtained by the same method as in Example 1 except that the raw material ratio and layer ratio of the void-containing layer A were changed as shown in Table 1 and the coating composition of the functional adhesive layer was changed as follows.
[0188] The solid content in the coating liquid of the compound constituting the functional easy-adhesion layer is as follows.
[0189] The total of the solid content contained in the functional easily-adhesive layer is set to 100 mass %.
[0190] Colloidal silica particles (E) (average particle size: 450 nm): 48.8% by mass
[0191] Cationic antistatic agent A: 2.1 mass%
[0192] Urethane resin B having a polycarbonate structure: 12.2% by mass
[0193] Blocked isocyanate crosslinking agent C: 12.2 mass%
[0194] ·Polyester resin Dw-1: 24.4 mass%
[0195] Silicone surfactant: 0.1% by mass
[0196] pH adjuster (sodium bicarbonate): 0.2 mass%
[0197] The mass ratio of urethane resin (B) / crosslinking agent (C) / polyester resin (Dw-1) is 25 / 25 / 50 / .
[0198] The above-mentioned functional adhesive layer was used, and the WET coating amount was changed to 10 g / m 2 In addition, the same method as in Example 1 was used to obtain a functional easy-adhesive layer having a thickness of 0.55 g / m after drying. 2 The functional easy-adhesive layer has a gloss value of 9.0% at 60-degree regular reflection, and is a functional easy-adhesive layer with excellent matte feel.
[0199] (Comparative Example 1)
[0200] In Example 1, the silicone resin in the void-containing layer A was changed to 0 ppm, the polyethylene terephthalate resin was changed to 93.08 mass %, and no functional easy-adhesion layer was provided. A void-containing polyester film was obtained by the same method as in Example 1. The void-containing polyester film of Comparative Example 1 had an apparent density exceeding 1.20 g / cm 3, therefore, the lightness and cushioning properties are poor. Due to the large mass, the manufacturing cost is also high. In addition, the total light transmittance of the polyester film containing voids in Comparative Example 1 is also high, and compared with Examples 1 to 5, the concealment is also poor, there is no functional easy-adhesive layer, so there is a lack of UV ink adhesion, and there is no antistatic property, so there are problems in handling such as static electricity causing the films to adsorb to each other.
[0201] (Comparative Example 2)
[0202] In Example 1, the ratio of the above-mentioned layer was set to 0%, and the same method as in Example 1 was used to obtain a polyester-based adhesive film containing voids. The total light transmittance is slightly higher, and the concealment is poor compared with Examples 1 to 5. In addition, the color tone b value is large, and the whiteness is slightly lower than that of Examples 1 to 5, and the degree of yellowing is strong. In addition, the polyester-based adhesive film containing voids in Comparative Example 2 has pinhole shrinkage defects observed in the appearance of the obtained functional adhesive layer due to the influence of the silicone resin. In addition, the UV ink applied to the functional adhesive layer also falls off due to the defects of pinhole shrinkage, resulting in poor adhesion. Comparative Example 2 cannot suppress the coating shedding in the processing step of the produced polyester-based adhesive film containing voids and the printing shedding in the subsequent steps.
[0203] (Comparative Example 3)
[0204] In Example 1, a void-containing polyester-based adhesive film was obtained by the same method as in Example 1 except that the raw material ratio of the void-containing layer A was changed as shown in Table 1. In the void-containing polyester-based adhesive film of Comparative Example 3, the apparent density was less than 0.80 g / cm 3 Therefore, the film itself has a weak stiffness and the surface strength is also reduced. The film forming property of Comparative Example 3 is inferior to that of Examples 1 to 5.
[0205] In summary, in the void-containing polyester-based easy-adhesive film of the present invention, by making the void-containing layer A contain a trace amount of silicone resin, the thermal degradation of the polypropylene resin can be suppressed during, for example, the processing step, and the void visibility can be maintained. Therefore, the void-containing polyester-based easy-adhesive film of the present invention has excellent adhesion, and even if the apparent density is 0.80 to 1.20, it has excellent lightness, film-forming properties, concealment, and whiteness. In particular, the void-containing polyester-based easy-adhesive film described in Examples 1 to 5 has excellent adhesion, and even if the apparent density is 0.80 to 1.10, it has excellent lightness, film-forming properties, concealment, and whiteness.
[0206] [Table 1]
[0207]
[0208] Industrial Applicability
[0209] As described above, the void-containing polyester-based easy-adhesive film of the present invention is excellent in lightness, film-forming properties, concealing properties, and whiteness, and has easy adhesion. Therefore, it is suitable for use as a substrate such as labels, cards, packaging materials, electronic materials, and release films used in the manufacture of polarizing plates or laminated ceramic capacitors.
Claims
1. A void-containing polyester-based easy-adhesive film, comprising a first covering layer B1, a void-containing layer A, and a second covering layer B2 laminated in sequence, wherein the first covering layer B1 comprises a polyester resin containing an inorganic pigment, the void-containing layer A contains voids inside, the second covering layer B2 comprises a polyester resin containing an inorganic pigment, and a functional easy-adhesive layer is provided on the first covering layer B1. The apparent density of the void-containing polyester easy-adhesive film is 0.80 g / cm 3 Above and 1.20g / cm 3 the following, The void-containing layer A includes a composition including a polyester resin, a polypropylene resin, and a silicone resin.
2. The void-containing polyester-based easy-adhesion film according to claim 1, wherein In the void-containing layer A, the content of the polydimethylsiloxane in the silicone resin is 1 ppm or more and 2500 ppm or less relative to the total mass of the void-containing layer A.
3. The void-containing polyester-based easy-adhesion film according to claim 1, wherein In the void-containing layer A, the content of the polydimethylsiloxane in the silicone resin is 0.005 mass % or more and 2.000 mass % or less relative to 100 mass % of the polypropylene resin.
4. The void-containing polyester-based easy-adhesion film according to claim 1, wherein The inorganic pigment in the first covering layer B1 and the second covering layer B2 is titanium oxide.
5. The void-containing polyester-based easy-adhesion film according to claim 1, wherein The ratio of the total thickness of the first covering layer B1 and the second covering layer B2 to the total thickness of the first covering layer B1, the void-containing layer A, and the second covering layer B2 is 6% or more and 40% or less. 6 . The void-containing polyester-based easy-adhesion film according to claim 1 , wherein the total light transmittance is 1% to 30%.
7. The void-containing polyester-based easy-adhesive film according to claim 1, wherein the apparent density is 0.80 g / cm 3 Above and 1.10g / cm 3 the following.
8. The void-containing polyester-based easy-adhesion film according to claim 1, wherein The functional easy-adhesion layer has a close contact residual area of 99% or more obtained by the following evaluation method. The remaining area of the seal is evaluated based on the following method: The functional easy-adhesive layer of the polyester-based easy-adhesive film containing voids was printed using UV ink [T&K TOKA Co., Ltd., trade name "BEST CURE (registered trademark) UV161 Blue S"] using a printer [Ming Manufacturing Co., Ltd., trade name "RI TESTER"], and then the film coated with the ink layer was irradiated with 40 mJ / cm using a high-pressure mercury lamp. 2 The ultraviolet rays are used to cure the UV-curing ink. Next, a 24 mm wide and 50 mm long piece of cellophane adhesive tape (CT405AP-24) manufactured by NICHIBAN is cut and completely attached using a handheld rubber roller in such a way that air is not mixed into the surface of the ink layer. Thereafter, the cellophane adhesive tape is peeled off vertically, and the residual area of the printed layer, i.e., the close-fitting residual area (%), is observed and calculated within an area of 24 mm × 50 mm.
9. The void-containing polyester-based easy-adhesion film according to claim 1, wherein The functional easy-adhesive layer contains an antistatic agent and has a surface resistivity of 1.0×10 13 Ω / sq or less.
10. The void-containing polyester-based easy-adhesion film according to claim 1, wherein The number of pinhole-like shrinkage holes in the functional easy-adhesion layer is 5 / m 2 the following, The number of pinhole-like shrinkage cavities in the functional adhesive layer was evaluated by visually observing the functional adhesive layer of the void-containing polyester adhesive film under a three-wavelength fluorescent lamp and counting the number of pinhole-like shrinkage cavities. 11 . The void-containing polyester-based easy-adhesive film according to claim 1 , which is used for labels, cards, packaging materials or release films.
Citation Information
Patent Citations
JP1974134755A
JP1979029550B1
White surface-roughened polyester film and its production
JP1990180933A
White polyester film
JP1990284929A
Microbubble-containing polyester film
JP1995017779B2